Issues of teacher professional learning within 'non-traditional' classroom environments. (November 2013) - Campbell, Matthew; Saltmarsh, Sue; Chapman, Amy; Drew, Christopher
In response to the demands of the '21st century learner', classroom environments are increasingly moving away from traditional models of a single-teacher isolated in their classroom. There is an advent of 'non-traditional' environments that challenge long-held practices in teaching. To support these changes there is a pressing need to create opportunities for professional learning. This article reports on a study undertaken within three primary schools that had recently adopted 'non-traditional' classroom environments. The study aimed to identify how these new spaces were shaping teaching practices and the challenges that they presented for professional learning. This article presents findings from this study with recommendations for how systems and schools can better manage the opportunities presented by these 'non-traditional' environments.